Targeting Inhibition of SmpB by Peptide Aptamer Attenuates the Virulence to Protect Zebrafish against Aeromonas veronii Infection - Liu, Peng; Huang, Dongyi; Hu, Xinwen; Tang, Yanqiong; Ma, Xiang; Yan, Rihui; Han, Qian; Guo, Jianchun; Zhang, Yueling; Sun, Qun; Liu, Zhu (Frontiers in Microbiology, 2017)
Aeromonas veronii is an important pathogen of aquatic animals, wherein Small protein B (SmpB) is required for pathogenesis by functioning as both a component in stalled-ribosome rescue and a transcription factor in upregulation of virulence gene bvgS expression. Here a specific peptide aptamer PA-1 was selected from peptide aptamer library by bacterial two-hybrid system employing pBT-SmpB as bait. The binding affinity between SmpB and PA-1 was evaluated using enzyme-linked immunosorbent assay. The key amino acids of SmpB that interact with PA-1 were identified. After PA-1 was introduced into A. veronii, the engineered strain designated as A. veronii (pN-PA-1) was more sensitive and grew slower under salt stress in comparison with wild type, as the disruption of SmpB by PA-1 resulted in significant transcription reductions of virulence-related genes. Consistent with these observations, A. veronii (pN-PA-1) was severely attenuated in model organism zebrafish, and vaccination of zebrafish with A. veronii (pN-PA-1) induced a strong antibody response. The vaccinated zebrafish were well protected against subsequent lethal challenges with virulent parental strain. Collectively, we propose that targeting inhibition of SmpB by peptide aptamer PA-1 possesses the desired qualities for a live attenuated vaccine against pathogenic A. veronii.